An urban field of dreams: professional baseball and the fruition of new - old Denver - Miller, Preston, author; Alexander, Ruth, advisor; Gudmestad, Robert, advisor; Dickinson, Greg, committee member; Didier, John, committee member (Colorado State University. Libraries, 2013)
This thesis examines how Coors Field framed the evolution of Denver's cultural geography and common identity between 1980 and 2010. I focus on the ballpark's connection to the process of "placemaking" as it unfolded between two adjacent "Old Denver" neighborhoods: North Larimer - a multicultural enclave that became the "Ballpark Neighborhood" - and the Lower Downtown historic district, whose founders bemoaned Denver's subsequent transformation into "Sports Town USA." As a contested icon, Coors Field affected notions of place, image, and inclusion for these neighborhoods and the city at large. Given this volatile context, I argue that its fruition highlighted what the Retro Ballpark Movement could and could not do for postmodern urban America. Many observers have heralded this ballpark project as an urban panacea, but an analysis of how ordinary Denverites perceived the new kind of city it left in its wake exposed a growing rift between baseball's working class mythos and the upscale nature of contemporary ballpark projects. Despite its instant success as an economic anchor, Coors Field ultimately contributed to the homogenization (or "Disneyfication") of "Old Denver" - a trend that clashed with baseball's democratic promise and previous notions of this downtown area as a diverse and authentic enclave. Utilizing local periodicals and government documents, I look at how this facility sprang from the hopes, dreams, and qualms of myriad individuals; the finished product representing a new dawn for some and a recurring nightmare for others. The narrative follows, as a central protagonist of sorts, Karle Seydel, an influential urban designer and neighborhood activist who should be recognized as the grassroots "Father of Coors Field." Seydel championed the project as a means to save North Larimer, guided its design, and dealt with its consequences. I wanted to offer a people's history of the "Blake Street Ballpark," and thus his experiences and opinions (as well as those of his allies and opponents) will guide my analysis of how an urban field of dreams contributed to Denver's reinvention as a new - old "city of leisure."